2010
DOI: 10.1097/aln.0b013e3181eaaef9
|View full text |Cite
|
Sign up to set email alerts
|

Acute Anemia Elicits Cognitive Dysfunction and Evidence of Cerebral Cellular Hypoxia in Older Rats with Systemic Hypertension

Abstract: Background Postoperative cognitive dysfunction occurs frequently after cardiac, major vascular, and major orthopedic surgery. Aging and hypertensive cerebrovascular disease are leading risk factors for this disorder. Acute anemia, common to major surgery, has been identified as a possible contributor to postoperative cognitive dysfunction. The effect of hypoxia upon cognition and the cellular and molecular processes involved in learning and memory has been well described. Cerebrovascular changes related to chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 51 publications
5
37
0
6
Order By: Relevance
“…In the absence of these responses, healthy young mice experience a shift in their mean lethal Hb concentration from 25 gÁL -1 to a higher value near 35 gÁL -1 . 21 Experimental models have shown that these hypoxic cellular responses are also upregulated during chronic anemia 27 and in older hypertensive rodents, 28 suggesting that they may have relevance to both the pediatric and the older adult patient populations that undergo anesthesia for surgical treatment. The overall conclusion from current experimental models strongly suggests that impaired oxygen delivery and tissue hypoxia contribute to increased mortality during acute anemia.…”
Section: Why Is Anemia Unsafe?mentioning
confidence: 99%
“…In the absence of these responses, healthy young mice experience a shift in their mean lethal Hb concentration from 25 gÁL -1 to a higher value near 35 gÁL -1 . 21 Experimental models have shown that these hypoxic cellular responses are also upregulated during chronic anemia 27 and in older hypertensive rodents, 28 suggesting that they may have relevance to both the pediatric and the older adult patient populations that undergo anesthesia for surgical treatment. The overall conclusion from current experimental models strongly suggests that impaired oxygen delivery and tissue hypoxia contribute to increased mortality during acute anemia.…”
Section: Why Is Anemia Unsafe?mentioning
confidence: 99%
“…Potential perioperative events that may negatively interact with preoperative leukoaraiosislacunae volume include acute anemia (60)(61)(62)(63), hypotension (64), oxygen desaturation (65)(66)(67), and the production of emboli. In our sample, we acquired valid emboli data on 15 of our surgery participants.…”
Section: Considerations For Neuropsychological Measures and Potentialmentioning
confidence: 99%
“…Such effects seem to be worse in aged patients, given the greater incidence of cognitive dysfunction in this population (Moller et al, 1998). This hypothesis was demonstrated in an experimental study by Li et al (2010), who showed the association between acute anemia (i.e. hemoglobin 5 g/dL) and age-dependent visual-spatial working memory and learning impairment in rats.…”
Section: Impact Of Anh On Brainmentioning
confidence: 95%
“…hemoglobin 5 g/dL) and age-dependent visual-spatial working memory and learning impairment in rats. They also showed an increase in hypoxia-inducible factor (HIF) and related molecular markers of cellular hypoxia, in the presence of normal systemic and local cerebral tissue oxygenation, which was more evident in older animals (Li et al, 2010).…”
Section: Impact Of Anh On Brainmentioning
confidence: 99%